Method for spontaneously passivating lower surface of perovskite thin film and application

By adding "4-(4-(4methoxyphenyl)-2-pyrrolidone" dopant to the perovskite precursor, the spontaneous passivation of the lower surface of the perovskite film is solved, and the middle and lower surfaces of the perovskite battery preparation are solved. Defects, simplify processes, reduce costs, and improve battery efficiency.

CN119403415APending Publication Date: 2025-02-07HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327159.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively passivate the defects of the lower surface of the perovskite film, resulting in complexity in the preparation process and increased costs, affecting the commercialization of perovskite batteries.

Method used

The dopant "4-(4methoxyphenyl)-2-pyrrolidone" is added to the perovskite precursor solution, and passivation of the defect is achieved by spontaneously depositing on the lower surface of the perovskite film.

Benefits of technology

This method simplifies the preparation process of perovskite batteries, reduces production costs, and improves the quality of perovskite films. The optimal efficiency of single junction batteries reaches 24.1%, and the optimal efficiency of components reaches 22.1%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403415A_ABST
    Figure CN119403415A_ABST
Patent Text Reader

Abstract

The invention provides a method for spontaneously passivating the lower surface of a perovskite thin film, which comprises the following steps of: adding 4-(4-methoxyphenyl)-2-pyrrolidone into a perovskite precursor solution, and preparing the perovskite thin film by using the 4-(4-methoxyphenyl)-2-pyrrolidone. The invention also provides an application of the method in preparation of a perovskite battery device and the perovskite battery device. A perovskite light absorption layer of the perovskite battery device adopts a perovskite film obtained after treatment by the method. The method has the advantages that (1) 4-(4-methoxyphenyl)-2-pyrrolidone is added into the perovskite precursor solution, a dopant in the prepared perovskite thin film can be spontaneously deposited on the lower surface of the perovskite thin film, passivation of defects on the lower surface of the perovskite thin film is effectively achieved, and the defects are reduced; (2) the operation is simple, the battery preparation process is simplified, and the cost is reduced; and (3) the efficiency corresponding to the perovskite solar photovoltaic device is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a method for spontaneously passivating the lower surface of a perovskite film and its application. Background Art

[0002] The photoelectric conversion efficiency of perovskite solar cells has reached 26.7%, showing great potential for commercial applications.

[0003] In perovskite films, the defect concentration on the lower surface is higher than that on the upper surface and the bulk phase. Therefore, it is particularly important to passivate the lower surface defects of perovskite films. Previous studies on the method of passivating the lower surface defects of perovskite films mainly involved preparing a passivation layer before depositing the perovskite film, which would complicate the preparation process of the battery, increase the preparation cost, and be detrimental to the commercialization of perovskite batteries.

[0004] Therefore, it is necessary to develop a simple and effective method to passivate the subsurface defects of perovskite films. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a simple and effective method for spontaneously passivating the lower surface of a perovskite film and its application.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] A method for spontaneously passivating the lower surface of a perovskite film, wherein a dopant "4-(4-methoxyphenyl)-2-pyrrolidone" is added to a perovskite precursor solution, and then the dopant is used to prepare a perovskite film.

[0008] As one of the preferred embodiments of the present invention, the specific operation is as follows:

[0009] (1) dissolving AX and BX2 in a solution at a stoichiometric ratio of 1:1 to obtain an undoped perovskite precursor solution;

[0010] (2) adding a dopant "4-(4-methoxyphenyl)-2-pyrrolidone" to an undoped perovskite precursor solution to prepare a doped perovskite precursor solution;

[0011] (3) Preparing a perovskite film using the prepared doped perovskite precursor solution.

[0012] As one of the preferred embodiments of the present invention, in step (1), A is a formamidinium ion (FA + ), methylamine ion (MA + ), cesium ion (Cs + ), dimethylammonium ion (DMA + ), phenylethylammonium ion (PEA +) and other monovalent cations; B is lead ion (Pb 2+ ), tin ions (Sn 2+ ), manganese ion (Mn 2+ ), Germanium ions (Ge 2+ ), copper ions (Cu 2+ ) and other divalent cations; X is a chloride ion (Cl - ), iodide ion (I - ), bromide ion (Br - ), acetate ion (Ac - ), thiocyanate ion (SCN - ), tetrafluoroborate ion (BF4 - ), hexafluorophosphate ion (PF6 - ) and other monovalent anions.

[0013] As one of the preferred embodiments of the present invention, in step (1), the solution is one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 2-methoxyethanol (2Me), N-methylpyrrolidone (NMP), N-cyclohexylpyrrolidone (CHP), ethanol, ethanolamine solution, γ-butyrolactone (GBL), dimethylacetamide (DMAC), N,N-dimethylpropylene urea (DMPU), and methylammonium acetate ionic liquid (MAAc).

[0014] As one of the preferred embodiments of the present invention, in step (1), the concentration of the undoped perovskite precursor solution obtained is 1.1 mol / L.

[0015] As one of the preferred embodiments of the present invention, in step (2), the concentration of the added dopant "4-(4-methoxyphenyl)-2-pyrrolidone" is 0.5 to 5 mg / mL, more preferably 2.5 mg / mL.

[0016] As one of the preferred embodiments of the present invention, in step (3), a perovskite wet film is first prepared using a doped perovskite precursor solution, and then the solvent in the wet film is extracted. Finally, the extracted film is annealed to obtain the desired perovskite film.

[0017] As one of the preferred embodiments of the present invention, the perovskite wet film is prepared by blade coating, slit coating, spin coating, inkjet printing, screen printing, spin coating or spray coating.

[0018] As one of the preferred embodiments of the present invention, the solvent in the perovskite wet film is extracted by nitrogen extraction, flash evaporation or spin coating volatilization.

[0019] An application of the above method for spontaneously passivating the lower surface of a perovskite film in the preparation of a perovskite battery device.

[0020] A perovskite cell device adopts a formal device structure or an inverted device structure;

[0021] In the formal device structure, from bottom to top, there are glass, conductive layer, electron transport layer, perovskite light absorption layer, hole transport layer, and back electrode;

[0022] In the inverted device structure, from bottom to top, there are glass, conductive layer, hole transport layer, perovskite light absorption layer, electron transport layer, and back electrode;

[0023] The perovskite light-absorbing layers in the formal device structure and the inverted device structure are both treated with the above-mentioned method for spontaneously passivating the lower surface of the perovskite film to obtain the perovskite film.

[0024] The advantages of the present invention compared to the prior art are:

[0025] (1) The present invention adds "4-(4-methoxyphenyl)-2-pyrrolidone" as a dopant in the perovskite precursor solution, and the dopant in the prepared perovskite film will spontaneously deposit on the lower surface of the perovskite film, effectively passivating the defects on the lower surface of the perovskite film and reducing the defects; in addition, the dopant will also increase the grain size and enhance the crystallinity;

[0026] (2) The method of the present invention is simple to operate, can simplify the preparation process of perovskite batteries, and reduce production costs;

[0027] (3) The perovskite film prepared based on the method of the present invention is suitable for single-junction solar cells and battery modules. The corresponding perovskite solar photovoltaic devices have high efficiency. The best efficiency of single-junction cells reaches 24.1%, and the best efficiency of modules reaches 22.1%. The present invention provides technical support for the large-scale preparation of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a schematic structural diagram of a perovskite solar cell assembly device in Example 1;

[0029] Figure 2 is a flow chart of the preparation of the perovskite solar cell module device in Example 1;

[0030] Figure 3 is a schematic diagram of the scraping process in Example 1;

[0031] Figure 4 is a physical picture of the perovskite film prepared in Example 1;

[0032] Figure 5This is a physical picture of the perovskite solar cell module finally obtained in Example 1;

[0033] Figure 6 is a schematic structural diagram of a single-junction perovskite solar cell device in Example 2;

[0034] Figure 7 is a flow chart of the preparation of a single-junction perovskite solar cell device in Example 2;

[0035] Figure 8 is a flow chart of the preparation of the perovskite solar cell module device in Example 3;

[0036] Fig. 9 is a flow chart of the preparation of the perovskite solar cell module device in Example 4;

[0037] Fig.10 is a flow chart of the preparation of the perovskite solar cell module device in Example 5;

[0038] Fig.11 is a schematic diagram of the structure of the perovskite solar cell assembly device in Example 6;

[0039] Fig.12 is a flow chart of the preparation of the perovskite solar cell module device in Example 6;

[0040] Fig.13 is a schematic structural diagram of a single-junction perovskite solar cell device in Example 7;

[0041] Fig.14 is a scanning electron microscope image of the thin film of the control group and the experimental group in Experimental Example 1 (in the figure, Figure a is the control group, and Figure b is the experimental group);

[0042] Fig.15 is the XRD pattern of the thin films of the control group and the experimental group in Experimental Example 1;

[0043] Fig.16 is the distribution diagram of 4-(4-methoxyphenyl)-2-pyrrolidone molecules inside the film in the experimental group of Experimental Example 1 (TOF-SIMS test);

[0044] Fig.17 This is a comparison of the photoelectric conversion efficiency of the perovskite single-junction cells in the control group and the experimental group in Experiment 2 (effective area: 0.09 cm 2 );

[0045] Fig.18 This is a comparison of the photoelectric conversion efficiency of the perovskite module cells in the control group and the experimental group in Experiment 3 (effective area: 12cm 2 ). DETAILED DESCRIPTION

[0046] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments. At the same time, the reagents, experimental equipment and experimental methods used in the following embodiments are conventional reagents, equipment and methods in the art unless otherwise specified, and will not be repeated.

[0047] Example 1

[0048] A perovskite solar cell component device (formal device structure) of this embodiment is a perovskite film prepared based on a blade coating method combined with a nitrogen extraction method.

[0049] The structure of the perovskite solar cell module device is as follows Figure 1 As shown, from bottom to top are glass Glass, conductive layer ITO, electron transport layer SnO2, perovskite light absorption layer Perovskite, hole transport layer Spiro-OMeTAD, back electrode Au, and the device also includes laser etching P1, P2, P3, and P4.

[0050] Its preparation process is as follows Figure 2 As shown, the following steps are included:

[0051] S1. Laser etching of the conductive layer ITO on the conductive glass (P1):

[0052] Etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 8us.

[0053] S2. Cleaning conductive glass:

[0054] Conductive glass of 6.5 cm × 6.5 cm size is cleaned by ultrasonic cleaning with detergent, deionized water, deionized water, deionized water, and ethanol in sequence. After cleaning, the glass is blown dry with a nitrogen gun or an air gun before use.

[0055] S3. Preparation of tin dioxide electron transport layer by spin coating:

[0056] a. Treat the cleaned conductive glass with a UV ozone machine for 30 minutes or a plasma surface treatment instrument for 10 minutes.

[0057] b. 30 mg of potassium chloride was dissolved in a mixed solution containing 2 g of tin oxide colloidal solution and 8 g of pure water, and stirred for 6 hours to prepare a tin oxide electron transport layer solution.

[0058] c. Drop the tin dioxide solution on the conductive glass and spin coat it at 6000r / min for 30s using a spin coater. Anneal it on a heating table at 95°C for 70min.

[0059] S4. Preparation of perovskite film by blade coating combined with nitrogen extraction method:

[0060] (1) The perovskite component (FAPbI3) 0.95 (MAPbBr3) 0.05 It was dissolved in a mixed solution of 2Me and CHP (V:V=1000:99) to prepare a 1.1 mol / L undoped perovskite precursor solution.

[0061] Specifically, 359 mg FAI, 963 mg PbI2, 12 mg MABr, 40 mg PbBr2, and 51 mg MACl were weighed and dissolved in a mixed solution of 198 ul CHP and 2000 ul 2Me.

[0062] (2) Add 5 mg of 4-(4-methoxyphenyl)-2-pyrrolidone to the undoped perovskite precursor solution and stir for 2 h to obtain a doped perovskite precursor solution.

[0063] (3) Preparation of perovskite thin films by scraping method.

[0064] Figure 3 Schematic diagram of the scraping process.

[0065] Before scraping: Use a UV-ozone instrument to treat the conductive glass surface coated with the electron transport layer for 30 minutes or use a plasma surface treatment instrument to treat it for 10 minutes to improve the wettability of the perovskite precursor solution on the conductive glass surface coated with the electron transport layer.

[0066] Scraping process: Place the conductive glass on the scraper platform and place the scraper on the conductive glass. Drop the perovskite precursor in the gap between the scraper and the conductive glass. Start the scraper, which pushes the scraper to move. At the same time, the scraper pushes the perovskite solution to coat the conductive glass. The wind knife that assists crystallization moves synchronously. Finally, a wet perovskite film is left on the conductive glass.

[0067] The scraping parameters are as follows: the amount of perovskite precursor solution used is 24 μL, and it is evenly dispensed 6 times with a pipette, with 4 μL used each time; the scraper reading height is 1160 μm; the conductive glass substrate height is 1000 μm; the scraper movement speed and the nitrogen air knife movement speed are 25 mm / s.

[0068] After scraping: transfer the wet perovskite film to a heating table for annealing at a temperature of 150°C for 10 minutes.

[0069] Figure 4This is a photo of the perovskite film prepared based on this embodiment.

[0070] S5. Preparation of Spiro-OMeTAD hole transport layer by spin coating:

[0071] Preparation of hole transport layer precursor solution: weigh 70 mg Spiro-OMeTAD, 30 μL 4-tert-butylpyridine (TBP), 18 μL lithium salt solution (400 mg / mL acetonitrile solution of TFSI-Li), and 9 μL cobalt (III) salt solution (500 mg / mL acetonitrile solution of FK209-Co(III)-TFSI), dissolve in 1 mL chlorobenzene and stir for 2 h.

[0072] When preparing the hole transport layer, 600 μL of Spiro-OMeTAD precursor was dropped on the perovskite film by a spin coater, and the spin coater was spun at a speed of 4000 r / min for 30 s.

[0073] S6, laser etching of electron transport layer, perovskite layer, hole transport layer (P2):

[0074] Before depositing the back electrode, the electron transport layer, perovskite layer and hole transport layer are etched using laser.

[0075] Laser etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 2us.

[0076] S7, evaporation to prepare Au back electrode:

[0077] Using an evaporator, 120 nm thick gold was evaporated as the back electrode.

[0078] S8, laser etching of electron transport layer, perovskite layer, hole transport layer, back electrode gold (P3):

[0079] After depositing the back electrode, the electron transport layer, perovskite layer, hole transport layer and back electrode are etched using laser.

[0080] Laser etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 3us.

[0081] S9, laser etching of conductive layer, electron transport layer, perovskite layer, hole transport layer, back electrode gold (P4):

[0082] After depositing the back electrode, the conductive layer, electron transport layer, perovskite layer, hole transport layer and back electrode on the conductive glass are etched using laser.

[0083] Laser etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 5us.

[0084] Figure 5 This is a picture of the perovskite solar cell module finally produced in this embodiment.

[0085] Example 2

[0086] A perovskite solar cell single junction device of this embodiment is a perovskite film prepared by a blade coating method combined with a nitrogen extraction method.

[0087] The structure of the perovskite solar cell single junction device is as follows Figure 6 As shown, from bottom to top are glass, conductive layer ITO, electron transport layer SnO2, perovskite light absorption layer Perovskite, hole transport layer Spiro-OMeTAD, and back electrode Au, and no laser etching structure is involved.

[0088] Its preparation process does not require laser etching process, see Figure 7 The other preparation processes are consistent with the component battery preparation in Example 1.

[0089] Example 3

[0090] A perovskite solar cell module device of this embodiment is basically the same as that of embodiment 1, except that: the preparation method of the perovskite film is a blade coating method combined with a flash evaporation method, such as Figure 8 shown.

[0091] Scraping process: Place the conductive glass on the scraper platform and place the scraper on the conductive glass. Drop the perovskite precursor in the narrow gap between the scraper and the conductive glass. Start the scraper, which pushes the scraper to move. At the same time, the scraper pushes the perovskite solution to coat the conductive glass. Finally, a wet perovskite film is left on the conductive glass. Place the wet perovskite film in the flash evaporation chamber and evacuate. When the vacuum reaches 10Pa, stop evacuating, fill with nitrogen, and take out the perovskite film.

[0092] From the flash evaporation device, the perovskite wet film was transferred to a heating stage for annealing at 150 °C for 15 min.

[0093] The scraping parameters are as follows: the amount of perovskite precursor solution used is 24 μL, and it is evenly dripped 6 times with a pipette, with 4 μL used each time; the scraper reading height is 1160 μm; the conductive glass substrate height is 1000 μm; the scraper moving speed is 25 mm / s.

[0094] The other operations are the same as those in Example 1.

[0095] Example 4

[0096] A perovskite solar cell module device of this embodiment is basically the same as that of embodiment 1, except that: the preparation method of the perovskite film is a slit coating method combined with a nitrogen extraction method, such as Fig. 9 shown.

[0097] The process of preparing perovskite thin film: place the substrate on the slit coating instrument and inject the perovskite precursor into the injection pump; the injection pump injects the perovskite precursor into the slit coating knife head and drips it onto the substrate.

[0098] Start the slit coating instrument, start the air knife at the same time, and move the slit coating platform and the conductive glass together, and finally coat a layer of perovskite wet film on the conductive glass. The parameters of slit coating are as follows: the size of the slit coating knife is 20cm, the distance between the slit coating knife and the substrate is 140μm; the moving speed of the slit coating platform is 5mm / s; the moving speed of the conductive glass is 5mm / s; the air knife is a nitrogen air knife, the pressure is 0.4MPa; the injection speed is 1μL / s.

[0099] The perovskite wet film was transferred to a heating stage for annealing at 150 °C for 15 min.

[0100] The other operations are the same as those in Example 1.

[0101] Example 5

[0102] A perovskite solar cell module device of this embodiment is basically the same as that of embodiment 1, except that: the preparation method of the perovskite film is an anti-solvent-free spin coating method, such as Fig.10 shown.

[0103] 600 μL of perovskite precursor was dropped onto the conductive glass and spun at 4000 r / min for 15 s by a spin coater. After the spin coating, the perovskite wet film was annealed on a heating stage at 150°C for 10 min.

[0104] The other operations are the same as those in Example 1.

[0105] Example 6

[0106] A perovskite solar cell module device (inverted device structure) of this embodiment is a perovskite film prepared by a blade coating method combined with a nitrogen extraction method.

[0107] The structure of the perovskite solar cell module device is as follows Fig.11 As shown, from bottom to top, they are glass, conductive layer ITO, hole transport layer PTAA, perovskite light absorption layer Perovskite, electron transport layer C 60and BCP, back electrode Ag, and the device also includes laser etching P1, P2, P3, and P4.

[0108] Its preparation process is as follows Fig.12 As shown, the following steps are included:

[0109] S1. Laser etching of the conductive layer ITO on the conductive glass (P1):

[0110] Etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 8us.

[0111] S2. Cleaning conductive glass:

[0112] Use detergent, deionized water, deionized water, deionized water, and ethanol ultrasonic cleaning in sequence. After cleaning, use a nitrogen gun or air gun to blow the glass dry before use.

[0113] S3. Preparation of PTAA hole transport layer by spin coating:

[0114] a. Treat the cleaned conductive glass with a UV ozone machine for 30 minutes or a plasma surface treatment instrument for 10 minutes.

[0115] b. Preparation of electron transport layer solution: Dissolve 2 mg PTAA in 1 mL chlorobenzene and stir for 2 h to prepare PTAA hole transport layer solution.

[0116] C. Drop 600μL of PTAA hole transport layer solution on the conductive glass, and spin coat it at 5000r / min for 30s using a spin coater. Anneal it on a heating table at 100℃ for 10min. Drop 600μL of DMF solution on PTAA, and spin coat it at 5000r / min for 30s using a spin coater. Anneal it on a heating table at 100℃ for 5min.

[0117] S4. Preparation of perovskite film by blade coating combined with nitrogen extraction method:

[0118] The preparation of the precursor solution is consistent with that in Example 1.

[0119] The process of preparing the perovskite film by the blade coating method is the same as that in Example 1.

[0120] S5, Evaporation C 60 , BCP preparation of electron transport layer:

[0121] 25nm C was deposited by evaporation. 60 and 7nm BCP.

[0122] S6, laser etching of hole transport layer, perovskite layer, electron transport layer (P2):

[0123] Laser Etching P2: Before depositing the back electrode, the hole transport layer, perovskite layer and electron transport layer are etched using laser.

[0124] Laser etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 2us.

[0125] S7, evaporation to prepare back electrode silver Ag:

[0126] Use an evaporator to evaporate 100nm thick silver Ag as the back electrode

[0127] S8, laser etching of hole transport layer, perovskite layer, electron transport layer, back electrode gold (P3):

[0128] After depositing the back electrode, the hole transport layer, perovskite layer, electron transport layer and back electrode are etched using laser.

[0129] Laser etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 3us.

[0130] S9, laser etching of conductive layer, hole transport layer, perovskite layer, electron transport layer, back electrode gold (P4):

[0131] After depositing the back electrode, the conductive layer, hole transport layer, perovskite layer, electron transport layer and back electrode on the conductive glass are etched using laser.

[0132] Laser etching parameters: laser wavelength, 355nm; laser etching speed, 500mm s -1 ; Laser frequency, 30kHz; Laser pulse width, 5us.

[0133] Example 7

[0134] A perovskite solar cell single junction device of this embodiment is a perovskite film prepared by a blade coating method combined with a nitrogen extraction method.

[0135] The perovskite solar cell single junction device structure is as follows Fig.13 As shown, from bottom to top, they are glass, conductive layer ITO, hole transport layer PTAA, perovskite light absorption layer Perovskite, electron transport layer C 60 and BCP, back electrode Ag, no laser etching structure involved.

[0136] The preparation process does not require a laser etching process, and other preparation processes are consistent with the component battery preparation of Example 6.

[0137] Comparative Example 1

[0138] The structure and preparation process of a perovskite solar cell component device in this comparative example are basically the same as those in Example 1, with the main difference being that the perovskite precursor solution for preparing the perovskite film adopts an undoped perovskite precursor solution, i.e., no 4-(4-methoxyphenyl)-2-pyrrolidone is added.

[0139] Comparative Example 2

[0140] The structure and preparation process of a perovskite solar cell single-junction device in this comparative example are basically the same as those in Example 2, with the main difference being that the perovskite precursor solution for preparing the perovskite film adopts an undoped perovskite precursor solution, i.e., no 4-(4-methoxyphenyl)-2-pyrrolidone is added.

[0141] Test Example 1

[0142] This test example is used to test the effect of "doping with 4-(4-methoxyphenyl)-2-pyrrolidone" on the quality of perovskite film.

[0143] The "undoped perovskite film" of comparative example 1 was used as a control group, and the "4-(4-methoxyphenyl)-2-pyrrolidone-doped perovskite film" of embodiment 1 was used as an experimental group, and the film qualities were tested respectively.

[0144] Scanning electron microscopy images of the control group and experimental group films are shown in Fig.14 As shown in the figure, it can be seen that compared with the undoped perovskite film in the control group, the grain boundaries of the experimental group "4-(4-methoxyphenyl)-2-pyrrolidone doped perovskite film" are reduced and the grain size is larger; usually, the defect concentration at the grain boundary is very high, so "grain boundary reduction" is conducive to reducing the defect concentration in the perovskite film.

[0145] The XRD patterns of the films in the control group and the experimental group are shown in Fig.15 As shown in the figure, it can be seen that the (001) peak intensity in the perovskite film of the experimental group is higher than that of the control group, indicating that the addition of 4-(4-methoxyphenyl)-2-pyrrolidone is beneficial to improving the crystallinity of the perovskite film.

[0146] also, Fig.16The distribution diagram of 4-(4-methoxyphenyl)-2-pyrrolidone molecules in the film in the experimental group. TOF-SIMS test shows that 4-(4-methoxyphenyl)-2-pyrrolidone mainly gathers at the bottom of the perovskite film, and 4-(4-methoxyphenyl)-2-pyrrolidone molecules have the function of passivating defects. Therefore, it is further proved that 4-(4-methoxyphenyl)-2-pyrrolidone molecules will spontaneously deposit at the bottom of the perovskite film during the crystallization process, passivate defects and improve film quality.

[0147] Test Example 2

[0148] This test example is used to test the effect of "doping with 4-(4-methoxyphenyl)-2-pyrrolidone" on the performance of perovskite single-junction cells.

[0149] The “perovskite solar cell single junction device” of comparative example 2 was used as a control group, and the “perovskite solar cell single junction device” of embodiment 2 was used as an experimental group, and the photoelectric conversion efficiency of the corresponding cells was tested respectively.

[0150] Comparison of photoelectric conversion efficiency of perovskite single junction cells between the control group and the experimental group Fig.17 As shown in the figure, it can be seen that when 4-(4-methoxyphenyl)-2-pyrrolidone is not added, the battery efficiency is 21.5%; after adding 4-(4-methoxyphenyl)-2-pyrrolidone, the battery efficiency increases significantly to 24.1%.

[0151] Test Example 3

[0152] This test example is used to test the effect of "doping with 4-(4-methoxyphenyl)-2-pyrrolidone" on the performance of perovskite component cells.

[0153] The “perovskite solar cell module device” of comparative example 1 was used as a control group, and the “perovskite solar cell module device” of embodiment 1 was used as an experimental group, and the photoelectric conversion efficiency of the corresponding cells was tested respectively.

[0154] Comparison of photoelectric conversion efficiency of perovskite module batteries in the control group and the experimental group Fig.18 As shown in the figure, it can be seen that when 4-(4-methoxyphenyl)-2-pyrrolidone is not added, the battery assembly efficiency is 19.1%; after adding 4-(4-methoxyphenyl)-2-pyrrolidone, the battery efficiency increases significantly to 22.1%.

[0155] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for spontaneously passivating the lower surface of a perovskite film, characterized in that: The dopant "4-(4-methoxyphenyl)-2-pyrrolidone" is added to the perovskite precursor solution, and then used to prepare the perovskite film.

2. The method for spontaneously passivating the lower surface of a perovskite film according to claim 1, characterized in that: The specific operations are as follows: (1) dissolving AX and BX2 in a solution at a stoichiometric ratio of 1:1 to obtain an undoped perovskite precursor solution; (2) adding a dopant "4-(4-methoxyphenyl)-2-pyrrolidone" to an undoped perovskite precursor solution to prepare a doped perovskite precursor solution; (3) Preparing a perovskite film using the prepared doped perovskite precursor solution.

3. The method for spontaneously passivating the lower surface of a perovskite film according to claim 2, characterized in that: In the step (1), A is one or more of formamidine ion, methylamine ion, cesium ion, dimethylammonium ion, and phenethylammonium ion; B is one or more of lead ion, tin ion, manganese ion, germanium ion, and copper ion; and X is one or more of chloride ion, iodide ion, bromide ion, acetate ion, thiocyanate ion, tetrafluoroborate ion, and hexafluorophosphate ion.

4. The method for spontaneously passivating the lower surface of a perovskite film according to claim 2, characterized in that: In the step (1), the solution is one or more of N,N-dimethylformamide, dimethyl sulfoxide, 2-methoxyethanol, N-methylpyrrolidone, N-cyclohexylpyrrolidone, ethanol, ethanolamine solution, γ-butyrolactone, dimethylacetamide, N,N-dimethylpropylene urea, and methylammonium acetate ionic liquid.

5. The method for spontaneously passivating the lower surface of a perovskite film according to claim 2, characterized in that: In the step (1), the concentration of the undoped perovskite precursor solution obtained is 1.1 mol / L; in the step (2), the concentration of the added dopant "4-(4-methoxyphenyl)-2-pyrrolidone" is 0.5-5 mg / mL.

6. The method for spontaneously passivating the lower surface of a perovskite film according to claim 2, characterized in that: In the step (3), a perovskite wet film is first prepared using a doped perovskite precursor solution, and then the solvent in the wet film is extracted. Finally, the film after the extraction treatment is annealed to obtain the desired perovskite film.

7. The method for spontaneously passivating the lower surface of a perovskite film according to claim 6, characterized in that: The perovskite wet film is prepared by blade coating, slit coating, spin coating, inkjet printing, screen printing, spin coating or spray coating.

8. The method for spontaneously passivating the lower surface of a perovskite film according to claim 6, characterized in that: The solvent in the perovskite wet film is extracted by nitrogen extraction, flash evaporation or spin coating volatilization.

9. Use of the method for spontaneously passivating the lower surface of a perovskite film as claimed in any one of claims 1 to 8 in the preparation of a perovskite battery device.

10. A perovskite battery device, characterized in that: Using a formal device structure or a reverse device structure; In the formal device structure, from bottom to top, there are glass, conductive layer, electron transport layer, perovskite light absorption layer, hole transport layer, and back electrode; In the inverted device structure, from bottom to top, there are glass, conductive layer, hole transport layer, perovskite light absorption layer, electron transport layer, and back electrode; The perovskite light-absorbing layers in the formal device structure and the inverted device structure are both perovskite films obtained by being processed by the method described in any one of claims 1 to 8.